Fostering Cross Cultural Confidence Transformative Insights from the Speak Up Program for Military Personnel - Abdullah Adnan, Mohamed; Noor Azlinda, Zainal Abidin; Nur Syafawati, Sabuan (UMPSA, 2023)
GAMBANG, 2 August 2023 - The culmination of an enriching training endeavour offered by the Centre for Modern Languages (CML) on 2 to 3 August 2023 was marked by the conclusion of the Speak Up! programme.